IMPLEMENTASI PRINSIP-PRINSIP SUPERVISI PENGAJARAN DALAM MENINGKATKAN KOMPETENSI PEDAGOGIK GURU PENDIDIKAN AGAMA ISLAM - Sri Mardiyah (Conciencia, 2015)
Nowadays, supervision activities still tend to be oriented to the supervision of the formal aspects-administration. It makes the atmosphere of a partnership between teachers and supervisors less created. Even psychologically, teachers felt burdened with the thought to be assessed. In fact, supervision activities will be effective when there is no feeling depressed replaced by an atmosphere of service delivery are informal. Another fact that many emerging is the implementation of supervision as nothing but nothing. This is the basis of the writing of this topic, especially on the application of the principles of supervision of teaching in order to improve the pedagogical competence of teachers and the factors that affect the implementation. To explore these issues, conducted a literature study. Data were collected from references theoretical and the results of studies into similar themes. The data are then analyzed Descriptive qualitative in order to obtain an overview of nature and facts about the implementation of the principles of supervision in schools. The results of the analysis and interpretation suggest that the principles of supervision of teaching has not been fully implemented and not lead to the provision of assistance and professional guidance to teachers of religion, especially to overcome the problems of teaching they face. The supervisor only occasionally conduct classroom observations. Likewise individual guidance, group discussions, and supervision activities of others, still very minimal. Some of the obstacles in the implementation of the supervision of the teaching are to time constraints, the ability of the supervisor, motivation supervisors, and teachers Low, as well as psychological barriers and structures.